H2 Generation with (Mixed) Plasmonic Cu/Au‐TiO2 Photocatalysts: Structure–Reactivity Relationships Assessed by in situ Spectroscopy. Issue 6 (14th February 2017) - Priebe, Jacqueline B.; Radnik, Jörg; Kreyenschulte, Carsten; Lennox, Alastair J. J.; Junge, Henrik; Beller, Matthias; Brückner, Angelika
Abstract: Monometallic Cu and bimetallic Cu/Au‐TiO2 catalysts were prepared by impregnation (IM) and reductive precipitation (RP) methods in sequential (SP) and simultaneous mode (CP) and tested for photocatalytic H2 generation from H2 O/methanol mixtures with visible (400–700 nm) and UV/Vis light (320–500 nm). Comprehensive studies by high‐resolution (HR)‐STEM, X‐ray photoelectron spectroscopy (XPS), and different in situ methods (X‐ray absorption near‐edge structure (XANES), UV/Vis, and EPR spectroscopy) revealed that IM leads to dispersed surface Cu species with no clear particle formation, which is poorly active under visible light, whereas plasmonic Cu 0 nanoparticles formed by RP are about three times more active under the same conditions. In Cu/Au‐TiO2 catalysts prepared by RP‐SP, highly dispersed Cu surface species boost H2 production under UV/Vis light, owing to the effective separation within TiO2 and electron trapping by Cu, whereas small Cu 0 and Au 0 particles remain widely separated. When Cu/Au‐TiO2 catalysts are prepared by RP‐CP, mixed Cu/Au particles of uniform size (4–8 nm) provide the highest H2 evolution rates under visible light, owing to effective surface plasmon resonance absorption. Abstract : All that glitters isn't gold : The impact of different metal deposition methods on light‐driven H2 production is studied. Au/Cu alloy particles formed by coprecipitation evolve much more H2 under visible light than separate Au 0 and Cu 0 particles formed by stepwise precipitation. The opposite is true under UV light.